The influence of Latin on Old English adjectival postposition - Grabski, Maciej (Research in Language, 2022)
The article is a systematic, corpus-based account of Latin’s influence on the position of Old English (OE) adnominal adjectives. While multiple studies on phrase-level syntax suggest that source-text interference may have been partly responsible for placing the adjective after the head noun, this observation has so far received little quantitative underpinning. The present article offers a detailed comparison of OE target noun phrases containing postnominal adjectives with their Latin counterparts to determine the exact extent to which this arrangement may have been a syntactic calque from a foreign language. The study has found that while a fair number of OE postposed adjectives did copy their Latin originals, their placement could be accounted for through reference to tendencies characteristic of OE (i.e. the adjective displays different degrees of “verbalness” or is part of a heavy phrase). Therefore, it appears that translated texts do not have to be excluded or treated with particular suspicion in studies concerned with the position of adnominal adjectives.